Diabetes, Diet-Health Behavior, and Obesity - Anders, Sven; Schroeter, Christiane (Frontiers in Endocrinology, 2015)
High-quality diets play an important role in diabetes prevention. Appropriate dietary adherence can improve insulin sensitivity and glycemic control and thus, contribute to lifestyle improvement. However, previous research suggests that dietary adherence is arguably among the most difficult cornerstones of diabetes management. The objectives of this study are (1) to estimate whether and to what extent individuals diagnosed with diabetes show significant differences in diet quality (HEI) compared to healthy individuals, (2) to quantify whether and to what extent diabetics experience significantly higher outcomes of Body Mass Index (BMI), and (3) to estimate whether and to what extent dietary supplementation impacts diabetes patient’s diet quality and/or BMI outcomes. We use data from the 2007-2008 U.S. National Health and Nutrition Examination Survey (NHANES). The NHANES is the primary, randomized, and nationally representative survey used to assess the health and nutritional status in the U.S. We apply Propensity Score Matching (PSM) to account for selection bias and endogeneity between self-reported diet and health behaviour (treatment) and BMI outcomes. We control for an individual’s BMI as to capture the impact of past dietary behavior in its impact on HEI. Matching results suggest that regular dietary supplement consumption is associated with significant lower BMI outcomes of almost 1 kg/m2. The close relationship between diabetes and obesity has been at the center of the diet-health policy debate across Canada and the U.S. Knowledge about this linkage may help to improve the understanding of the factors that impact dietary choices and their overall health outcomes, which may lead to a more efficient and effective promotion of dietary guidelines, healthy food choices and targeted consumer health and lifestyle policies.